Impact of antibiotic prophylaxis on urinary tract infection recurrence in children: Rapid review - Potvin, Elyse; Adams, Kelsey; Barrieras, Diego; Bolduc, Stephane; Quach, Caroline (Canadian Urological Association Journal, 2024)
INTRODUCTION: Given the potential consequences associated with urinary tract infections (UTIs), it has become standard practice to use continuous antibiotic prophylaxis (CAP) in children, even if controversial. We reviewed the effectiveness of CAP on recurrent UTI in a pediatric population to determine if equipoise remains and allows for a placebo control group to study the effectiveness of the vaccine MV140. METHODS: We completed a rapid review. We searched Medline, Embase and the Cochrane Library and data extraction was completed by a single reviewer. Our search criteria were 2005–2022, English and French language, randomized controlled trials (RCTs) and systematic reviews only. The population was 19 years and younger, including: vesicoureteral reflux (VUR), congenital anomalies of the kidneys and urinary tracts (CAKUT), and bladder and bowel dysfunction (BBD). RESULTS: Three RCTs and three systematic reviews found a benefit for CAP, mostly for a population with VUR, and those with severe VUR have more benefit. Most studies were not able to show a difference in the rate of UTIs or new renal scars (NRS). Three RCTs found a deleterious effect with CAP. Other studies were able to prove a benefit for patients with dilatation of the urinary tract without obstruction and high-grade VUR combined with BBD. The major adverse event found was antimicrobial resistance. CONCLUSIONS: High-risk patients benefit from CAP. The potential consequences of UTIs makes it unethical to use a placebo-only control group for them; however, CAP use seems difficult to justify in a low-risk population.